Formulation of Hylocereus Polyrhizus Caulis Ekstract as Blush On - Rahmawatia, Rida; Suci, Panji Ratih; N.H.S., Cikra Ikhda (Proceedings of International Conference on Biology and Applied Science; Vol 1 No 1 (2019): The First Proceedings of International Conference on Biology and Applied Science, 2019)
Abstract. Dragon fruit peel has properties as natural dyes. Red dragon fruit peel contains flavonoids which have uses instead of synthetic dyes. This study aims to fromulate red dragon fruit peel as a blush on.This research was started by making red dragon fruit peel simplicia (Hylocereus polyrhzus), then extracting with mamceratin method using 70% ethanol solvent. The ectract is formulated with variations in concentrations of 5%, 10%, 15%. Phytocemical screening and blush on formulations. Physical quality tests which include homogeneity test, pH test, fragility test, preference test. The results of the study were analyzed using ANOVA or Analysis of Variance. The results showed that blush on extract of red dragon fruit peel can be made with the best formulation of kaolin (8%), zinc oxyde (4,74%), nipagin (1%), liquid paraffin (2,66%), and talk (ad 100%). Formulations with a concentration of 5%,10%,15% show the best physical quality.The conclucion of this study is dragon fruit bark extract formulated as a blush on with a concentration of 5%, 10%, 15% which has the best physical quality test.